Expression Profiling and Glycan Engineering of IgG Subclass 1–4 in Nicotiana benthamiana - Kallolimath, Somanath; Hackl, Thomas; Gahn, Raphaela; Grünwald-Gruber, Clemens; Zich, Wilhelm; Kogelmann, Benjamin; Lux, Anja; Nimmerjahn, Falk; Steinkellner, Herta (Frontiers in Bioengineering and Biotechnology, 2020)
IgG, the main serum immunoglobulin isotype, exists in four subclasses which selectively appear with distinctive glycosylation profiles. However, very little is known about the biological consequences mainly due to the difficulties in the generation of distinct IgG subtypes with targeted glycosylation. Here, we show a comprehensive expression and glycan modulation profiling of IgG variants in planta that are identical in their antigen binding domain but differ in their subclass appearance. While IgG1, 2 and 4 exhibit similar expression levels and purification yields, IgG3 is generated only at low levels due to the in planta degradation of the heavy chain. All IgG subtypes are produced with four distinct N-glycosylation profiles, differing in sugar residues previously shown to impact IgG activities, i.e. galactosylation, sialylation and core fucosylation. Affinity purified IgG variants are shown to be fully assembled to heterodimers but display different biochemical/physical features. All subtypes are equally well amenable to targeted glycosylation, except sialylated IgG4 which frequently accumulates substantial fractions of unusual oligo-mannosidic structures. IgG variants show significant differences in aggregate formation and endotoxin contamination which are eliminated by additional polishing steps (size exclusion chromatography, endotoxin removal treatments). Collectively we demonstrate the generation of 16 IgG variants at high purity and large glycan homogeneity which constitute an excellent toolbox to further study the biological impact of the two main Fc features, subclass and glycosylation.